IMPLEMENTATION OF THE WEBSITE-BASED SCHOOL-BASED SPP PAYMENT BILLING APPLICATION - Harahap, Ricky Ramadhan; Novelan, Muhammad Syahputra (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
In the SPP payment system at SMK Negeri 9 Medan, it is currently still being done manually, namely by means of transactions in cash and handwritten notes, thus slowing down work in the process of paying spp bills. With this, the SPP payment process has not run optimally. For this reason, it is necessary to have an SPP bill payment application to make it easier to make payments digitally. The system is designed using the PHP programming language and using the MySQL server database. The purpose of the system is to make it easier to archive spp bill payment data. It is hoped that the application will maximize admin work so that the target of delivering information and work can run more efficiently and effectively.